Pengaruh Literasi Keuangan, Risiko Transaksi dan Kemudahan Terhadap Minat Penggunaan QRIS Pada Umkm di Sampang - Anisah, Siti; Amaniyah, Evaliati (DINASTI RESEARCH, 2024)
Globally, digital payments are becoming trend, and new innovations are being developed to make financial transactions easier. In Indonesia, a financial technology for payments called Quick Response Code Indonesian Standard (QRIS) has gained widespread acceptance. Although there are many QRIS features available to promote financial digitalisation and assist MSMEs in the digital age, some MSMEs have challenges and feel less productive when using QRIS. This research sought to determine how MSMEs in Sampang were interested in using QRIS in relation to financial literacy, transaction risk, and ease of use. This research employs a quantitative approach, gathering information from 100 MSME QRIS users in Sampang via a questionnaire. Based on the study's findings, it can be said that financial literacy, transaction risk, does not affect on MSME’s interest in using QRIS and ease of use have a positive and significant impact on MSMEs' interest in using QRIS in Sampang. Additionally, financial literacy, transaction risk, and ease of use all have a positive and significant impact on MSMEs' interest in using QRIS in Sampang.